Metastases From Nested Variant Urothelial Carcinoma of the Urinary Bladder in Pancreatic Allograft Mimicking Graft Rejection - Wang, Jue (Elmer Press, 2012)
While not an uncommon tumor, urothelial carcinoma of the urinary bladder is rare in bladders draining pancreatic allografts. A case of urothelial carcinoma directly involving a pancreatic allograft with metastasis that occurred in a 49-year-old pancreas and kidney transplant recipient is described. Her initial clinical presentation and findings of CT scan of the abdomen suggested pancreatitis with features worrisome for rejection. A biopsy of her pancreatic allograft contained poorly differentiated carcinoma and cystoscopic biopsy disclosed an invasive high grade urothelial carcinoma arising in the background of extensive urothelial carcinoma in situ. Exploratory laparotomy revealed that the tumor invaded the right ovary and fallopian tube, cecum, and allograft with extensive retroperitoneal involvement. She underwent en bloc resection of distal ileum and cecum, resection of transplant pancreas, partial cystectomy, ileocolostomy anastomosis, and right salpingo-oophorectomy. Postoperatively, the patient was treated with four cycles of carboplatin and gemcitabine. She ultimately succumbed to her disease approximately 1 year after diagnosis. This case should alert physicians and radiologists to be aware of atypical presentation of urothelial carcinoma in bladder-drained pancreas grafts, the aggressiveness of such lesions, and the need for early biopsy to avoid diagnostic confusion with rejection. KEYWORDS: Bladder cancer; Nested variant of urothelial carcinoma; Pancreas and kidney transplantation